An overview of research efforts to understand the effects of underwater sound on cetaceans - Shane Guan; Tiffini Brookens (Water Biology and Security, 2023)
Cetaceans are aquatic mammals living in an environment that is more suited for hearing than vision. As such, their sensory systems largely utilize acoustic cues for navigation, communication, foraging, and predator avoidance. However, the elevation of underwater sound levels from increased human activities has adversely affected cetaceans’ use of sound to perform vital life functions. To address those impacts, scientific studies have been conducted to understand the behavioral, psychoacoustical, physiological, and physical responses by cetaceans that have been exposed to anthropogenic sound. These studies range from captive experiments involving auditory thresholds and noise-induced threshold shifts, to field observations of behavioral disturbance from sound exposure, to post-mortem examinations of physical manifestations in stranded animals. Over the years, results from these studies have assisted regulatory agencies in developing a series of criteria and thresholds for cetacean conservation and management around the world. This paper provides a high-level overview of worldwide research efforts that have been dedicated to understanding the effects of underwater sound on cetaceans. The review is not intended to be exhaustive but rather to capture major efforts and significant findings in this field. In addition, the review excludes synthesis studies and modeling exercises that do not involve direct research on target species.